Evaluation of Future Battery Electric Vehicles as an Environmentally Friendly Transportation Means: A Review - Matalata, Hendi; Syafii, Syafii; Hamid, Muhammad Imran (LPPM Universitas Andalas, 2023)
The climate challenge is an energy challenge. thus, policymakers around the world are trying to accelerate the adoption of clean energy technologies. The Global Energy Review said that global CO2 emissions from energy combustion in 2021 reached the highest annual level with an increase of 6% from 2020, The automotive sector is very important to achieve net zero global emissions by 2050 based on the agreement with the world in the Scenario Net Zero Emissions by 2050. in which in 2035 sales of internal combustion engine cars (ICE) will be stopped. In this case, of course, electric vehicles are an alternative to the field of future land transportation that uses batteries as fuel that utilizes renewable energy as a charger for electric vehicles. Electric vehicle charging infrastructure (EVCI) is a key driver of increased electrification mobility shifting away from internal combustion engines given that the specific geographical distribution of a region and its demographics are factors influencing the adoption of electric vehicles. This paper was written to review the state-of-the-art of Battery Electric Vehicle (BEV), a PV energy source in terms of renewable energy utilization, energy generation, batteries, and charging stations. PV generation is extensively reviewed, and although this research is quite extensive, some gaps need to be investigated for further research on commercial and residential aspects as a means of operating batteries for electric vehicle charging stations based on PV and BESS (Battery Energy Storage System). Regulations on the use of battery electric vehicles as an environmentally friendly means of transportation will grow based on government policies from each country